AIDS in Gynecology and Obstetrics - Gotuzzo, Eduardo (2015)
The stage of development of the epidemic of acquired immunodeficiency syndrome (AIDS) is changing in Latin America. There are several patterns of transmission. In Brazil and Mexico it is multifactorial and where blood transfucciones are made of "informal" way represent more than 10 to 15% of cases reported by these countries. Moreover, drug users who share needles and syringes represent over 60% of cases in Argentina and Puerto Rico, like Spain and Italy. In Central America (Honduras, Guatemala, Dominica Republic), the pattern is 70% heterosexual and homosexual transfusions and represent less than 25% of cases.